The Implementation of Problem Based Learning Model to Improve Reading Comprehension Achievement - Evi Rosmiyati (Politeknik Negeri Sriwijaya, 2021)
The purpose of the study was to know whether or not it was effective to improve reading comprehension achievement by implementing Problem Based Learning (PBL) model of the eighth graders of State Junior High School 3 of Lempuing OKI. In doing this research pre-experimental method with one group pretest-posttest design was used. The population of this study was all the eighth grade students of State Junior High School 3 of Lempuing OKI with the total number 115 students and the samples were 29 students in experimental group from VIII.1 class taken by cluster random sampling. The data were collected through reading comprehension test in multiple choice questions and analyzed by using matched t-test formula. The findings of the study showed that there was a significant difference between the students’ score in the pretest and posttest. The students’ average score in posttest was 75, higher than the students’ score in pretest which was 60.43. The result of the matched t-test was 19.69 that exceded its critical value of the t-table 1.701. It means that the implementation of PBL model was effective to improve reading comprehension achievement of the eighth graders of State Junior High School 3 of Lempuing OKI. Keywords: Reading comprehension, narrative text, problem based learning